Voto e fecundidade no Brasil: o efeito do processo eleitoral durante o regime militar sobre a mudança de comportamento reprodutivo brasileiro - Everton Emanuel Campos de Lima (2010)
This PhD-dissertation intended to explore the relationship between the suffrage in the 70s and the Brazilian fertility behavior. This association between electoral outcomes and fertility was never studied in Brazil before. During this period of analysis, the electoral behavior is assumed to be a proxy of a succession of linked social processes that might probably lead to distinguished fertility levels across the Brazilian municipalities. The results of analysis also associated the electoral outcomes to many socioeconomic and cultural changes, which later might affect the institutional arrangements, the community and family structures. This study is based on three distinguished analyses. First, this PhD-dissertation explored the spatial fertility variability across the Brazilian municipalities in 1980, and its association with the aggregated spatial electoral distribution of the Movimento Democrático Brasileiro (MDB) voters in 1976. Second, it is showed the existence of a negative relationship between the communitarian electoral behaviors and the variability in individual as well as communitarian fertility levels in 1980. At last, this study illustrated that the variability in fertility outcomes in 1991 and in 2000 kept a negative relationships with the Brazilian electoral results from the past. These results might also indicate the beginning of the individualization process, the end of the colonel communitarian power over the individual reproductive and political choices. This process might also constitute the foundation of a Brazilian civil society, the rise of the individual freedom to change the natural order of things. Furthermore, it is also showed how this new individualistic reproductive behavior reached in time other spatial areas initially not affected by the ideational changes initiated in the 70s.